A régiótörténet-írás néhány kérdése a Kárpát-medence régiói sorozat kapcsán - Kugler, József (Közép-Európai Közlemények, 2008)
The Hungarian Academy of Science Centre of Regional Studies started its Carpathian Basin Regions series in 2003 with the aim of revealing how this economic region could integrate into the spatial system of the EU. The series present in each volume a region according to uniformed editorship in order to get to know the past, present and the future of the area even more perfectly. The historical part is organically involved in each volume. The authors took the first step for creating the missing Hungarian region-historiography.